2017
DOI: 10.1038/cdd.2017.133
|View full text |Cite
|
Sign up to set email alerts
|

Atg2A/B deficiency switches cytoprotective autophagy to non-canonical caspase-8 activation and apoptosis

Abstract: Autophagosomal membranes are emerging as platforms for various cell survival and death signaling networks beyond autophagy. While autophagy-dependent cell death has been reported in response to a variety of stimuli, the underlying molecular mechanisms remain far from clear. Here, we demonstrate that inhibition of autophagosome completion by Atg2A/B deletion accumulates immature autophagosomal membranes that promote non-canonical caspase-8 activation in response to nutrient starvation via an intracellular death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 61 publications
7
54
0
1
Order By: Relevance
“…This is consistent with the observation in D. melanogaster Atg2 mutant cells that p62 extensively colocalizes with Atg9 but isolation membranes (phagophores) were only rarely observed around p62 structures [11,12]. Recently, another group also established ATG2A/B DKO THP-1 cells [9]. In contrast to our observation, these authors reported that immature autophagosomelike structures were generated in these cells.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with the observation in D. melanogaster Atg2 mutant cells that p62 extensively colocalizes with Atg9 but isolation membranes (phagophores) were only rarely observed around p62 structures [11,12]. Recently, another group also established ATG2A/B DKO THP-1 cells [9]. In contrast to our observation, these authors reported that immature autophagosomelike structures were generated in these cells.…”
Section: Discussionsupporting
confidence: 93%
“…The activation of apoptosis-related caspase can degrade autophagy-related proteins, thus inhibiting autophagy in tumor cells (Man et al 2017, Tang et al 2017. However, whether the apoptosis could regulate autophagy in germ cells in hypoxia remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…To generate a lentiviral vector encoding human VPS28, the VPS37A cDNA at the XhoI–NotI site in pCDH1-CMV-GFP-FL was replaced to the human VPS28 cDNA amplified from the plasmid pQTEV-VPS28 using the primer 5′-TAT​ACT​CGA​GGA​TTT​CAT​GGG​ATC​CCA​GCC-3′ and 5′-TCG​AGC​GGC​CGC​TCA​GGC​ATG-3′. For the tandem fluorescent-tagged VPS37A (RFP-GFP-VPS37A) expression constructs, the EGFP-LC3 cassette in tfLC3 (pCDH-RFP-EGFP-LC3; Tang et al, 2017) was replaced to GFP-FL or GFP-ΔPUEV at the Age1–Bamh1 site. All other reagents were obtained from the following sources: autoMACS Rinsing Solution (130–091-222), Miltenyi Biotec; BafA1 (B-1080), LC Laboratories; BSA (126575), EMD Millipore; MIL (AF488-conjugated, G1001; AF660-conjugated, G8471), Promega; MPL (TMR-conjugated, G8251), Promega; normal goat serum (G9023), Sigma-Aldrich; Nucleofector Kit V (VCA-1003), Lonza; PFA (15710), Electron Microscopy Sciences; recombinant human EGF (PHG0311), Invitrogen; and XF Plasma Membrane Permeabilizer/recombinant perfringolysin O mutant (102504–100), Seahorse Bioscience.…”
Section: Methodsmentioning
confidence: 99%